Co‐Quenching Effect between Lanthanum Metal–Organic Frameworks Luminophore and Crystal Violet for Enhanced Electrochemiluminescence Gene Detection. Issue 45 (4th October 2021) - Gao, Huan; Wei, Xuan; Li, Meize; Wang, Lei; Wei, Tianxiang; Dai, Zhihui
Abstract: Exploring new electrochemiluminescence (ECL) luminophores to construct high‐efficiency sensing systems is always a hot direction for developing ECL sensors. Compared with other luminophores, metal–organic frameworks (MOFs) exhibit high mass transfer ability for accelerating the reactivity in its pore channels, which is conducive to improving the performance of ECL sensors. In this work, La 3+ ‐BTC MOFs (LaMOFs) are prepared as the highly active reactor and novel ECL luminophore. On this basis, a novel co‐quenching effect mechanism is proposed based on double‐stranded DNA (dsDNA) triggered cooperation between LaMOFs and crystal violet (CV) molecules. Under the confined pore channels of LaMOFs, CV can play an important role as the photon‐acceptor due to the matched absorption spectrum with the ECL spectrum of LaMOFs, and the electron‐acceptor on account of its lowest unoccupied molecular orbital level. Based on the proposed co‐quenching effect mechanism, a constructed ECL gene sensor shows good assay performance toward p53 gene in the detection range of 1 pm to 100 nm with a detection limit of 0.33 pm . The co‐quenching effect integrating LaMOFs with CV is expected to be a versatile approach in the construction of ECL gene sensor, which has good prospect in expanding the application range of ECL technology. Abstract : A double‐stranded DNA bridged electrochemiluminescence (ECL) co‐quenching effect between lanthanum metal–organic frameworks (LaMOFs) luminophore and crystal violet is fabricated based on the electron and energy transfer happened in one system. The reactivity of the system is accelerated in the special reaction zone of micropore channels provided by LaMOFs, thus achieving the enhanced performance of ECL gene sensor.